2020
DOI: 10.21764/maeuefd.550343
|View full text |Cite
|
Sign up to set email alerts
|

Üni̇versi̇te Öğrenci̇leri̇ni̇n Benli̇k Ayrimlaşmasi, Özgeci̇li̇k, İç-Diş Kontrol Odaği Ve Pozi̇ti̇f-Negati̇f Duygu Düzeyleri̇ Arasindaki̇ İli̇şki̇leri̇n İncelenmesi̇

Abstract: Özet: Bu çalışmanın amacı, üniversite öğrencilerinde benlik ayrımlaşmasının, özgecilik, iç-dış kontrol odağı ve pozitif-negatif duygu düzeylerini yordamadaki rolünü incelemektir. Araştırmanın çalışma grubu, 2018-2019 eğitim-öğretim yılında, Uşak Üniversitesi, Eğitim Fakültesi'nin çeşitli bölümlerinde öğrenim görmekte olan ve araştırmaya gönüllü olarak katılmayı kabul eden 196'sı kız (%61,8), 121'i erkek (%38,2) olmak toplam 317 üniversite öğrencisinden oluşmaktadır. Katılımcıların benlik ayrımlaşması düzeyleri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…To our knowledge, no prior research has focused on the linkage between emotional expression (versus emotion regulation or emotion types/levels) and DoS; however, the current generation of Turkish couples are able to differentiate themselves from their parents, create couple identity and are more able to communicate and draw boundaries with the outside world (Zeytinoğlu-Saydam, Erdem & Söylemez, 2020). Furthermore, a study conducted in Turkish culture (Mert & Kahraman, 2020) found a substantial association between DoS and positive-negative emotion levels. The results provided evidence of the relationship between DoS and emotional expression in collectivist cultures as well.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no prior research has focused on the linkage between emotional expression (versus emotion regulation or emotion types/levels) and DoS; however, the current generation of Turkish couples are able to differentiate themselves from their parents, create couple identity and are more able to communicate and draw boundaries with the outside world (Zeytinoğlu-Saydam, Erdem & Söylemez, 2020). Furthermore, a study conducted in Turkish culture (Mert & Kahraman, 2020) found a substantial association between DoS and positive-negative emotion levels. The results provided evidence of the relationship between DoS and emotional expression in collectivist cultures as well.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with self-differentiation can experience their own preferences. They are less affected by their environment emotionally (Mert & Kahraman, 2020). Thus, drawing on these two theories, this study attempts to extend CCT by depicting the potential association between DoS, career adaptability, and job, marital, and life satisfaction.…”
mentioning
confidence: 99%